Oxidation and Degradation of WS2 Monolayers Grown by NaCl-Assisted Chemical Vapor Deposition: Mechanism and Prevention. Issue 39 (29th September 2021) - Chang, Yao-Pang; Li, Wei-Bang; Yang, Yueh-Chiang; Lu, Hsueh-Lung; Lin, Ming-Fa; Chiu, Po-Wen; Lin, Kuang-I
Abstract : Adjusting the orientation of the sapphire substrate to align the gas flow direction in the NaCl-assisted CVD process can improve the stability of monolayer WS2 . Abstract : The preservation of two-dimensional WS2 in the environment is a concern for researchers. In addition to water vapor and oxygen, the latest research points out that degradation is directly related to light absorption. Based on the selection rules of nonlinear optics, two-photon absorption is dipole forbidden in the exciton 1s states, but second-harmonic generation (SHG) is allowed with virtual transitions. According to this mechanism, we proved that SHG is an optical detection method with non-photooxidative damage and energy characteristics. With this detection method, we can explore the oxidation and degradation mechanisms of WS2 grown by NaCl-assisted chemical vapor deposition in its original state. The WS2 monolayers that use NaCl to assist in growth have undergone different degradation processes, starting to oxidize from random positions in the triangular flake. We use a photocatalytic reaction to explain the photo-induced degradation mechanism with sulfur vacancies. It was further found that WS2 grown with NaCl assistance is hydrolyzed in a dark and high-humidity environment, which does not occur in pure WS2 . Finally, we demonstrated that changing the direction of the sapphire substrate relative to the gas flow direction to grow NaCl-assisted WS2 can greatly improve its stability in the ambient atmosphere, even when exposed to light. The optimal geometric structures and ground state energies are investigated by the density functional theory-based calculations. According to the orientation and symmetry of NaCl-assisted WS2, we can expect that it will have a better growth quality when the gas flow direction is perpendicular to the [112̄0] direction of the sapphire substrate. This contributes to the nucleation and subsequent growth of NaCl-assisted WS2 . This research provides a more stable optical inspection method than other established methods and greatly improves the operational stability of NaCl-assisted WS2 under environmental conditions.